The Effectiveness of the Deep Learning Curriculum-Based Numbered Heads Together (NHT) Model in Improving Quadratic Function Problem-Solving Skills among Madrasah Aliyah Students - Umi Wasita; Nurwiani (Darul Yasin Al Sys, 2026)
Mathematical problem-solving is a fundamental competency in mathematics education; however, students continue to experience difficulties in solving problems involving quadratic functions. This condition underscores the need for an instructional approach that strengthens conceptual understanding while promoting active and meaningful student engagement. This study examined the effectiveness of a Deep Learning Curriculum (DLC)-based Numbered Heads Together (NHT) model in improving the mathematical problem-solving skills of Madrasah Aliyah students. A quantitative quasi-experimental approach with a nonequivalent control group design was employed, involving 32 students selected through purposive sampling. Data were collected using a mathematical problem-solving test and analyzed using an independent-samples t test, normalized gain (N-Gain), and Cohen’s d effect size. The findings indicate that students in the experimental group demonstrated significantly higher problem-solving performance, greater learning gains, and a stronger instructional effect than those in the control group. These results confirm that the DLC-based NHT model is effective in enhancing students’ mathematical problem-solving skills in quadratic function learning. The study contributes empirical evidence supporting the integration of meaningful and collaborative learning principles within cooperative mathematics instruction. Practically, the findings provide an alternative student-centered instructional strategy for supporting the implementation of the Merdeka Curriculum and improving students’ mathematical problem-solving competencies.